Effects of Renal Denervation via Renal Artery Adventitial Cryoablation on Atrial Fibrillation and Cardiac Neural Remodeling - Wei Wang; Zhaolei Jiang; Rongxin Lu; Hao Liu; Nan Ma; Jie Cai; Min Tang; Ju Mei (Cardiology Research and Practice)
Introduction. Catheter-based renal denervation (RDN) could reduce cardiac sympathetic nerve activity (SNA) and inhibit atrial fibrillation (AF). However, the reliability is uncertain, because the renal sympathetic nerves are mainly distributed in the adventitial surface of the renal artery. Objective. The aims of this study were to test the hypothesis that renal artery adventitial ablation (RAAA) definitely had the effects of RDN and to study the effects of RDN via renal artery adventitial cryoablation (RAAC) on AF and cardiac neural remodeling. Methods. Twenty beagle canines were randomly assigned to two groups: the left RDN group (LRDN, n=10), which underwent left RDN via RAAC; the Sham group (n=10). After 2 months of postoperative recovery, AF vulnerability, AF duration, and histological examination were performed in both groups. Results. Compared with the Sham group, left stellate ganglion (LSG) tissue fibrosis was increased in the LRDN group. LRDN significantly increased the percentage of TH-negative ganglionic cells and decreased the density of TH-positive nerves in the LSG (P<0.001). Also, the densities of TH-positive nerves and GAP43 immunoreactivity within the left atrium (LA) were significantly decreased in the LRDN group (P<0.05). After LA burst pacing, all 10 canines (100%) could be induced AF in the Sham group, but only 4 of 10 canines (40%) could be induced AF in the LRDN group (P=0.011). The percentage of LA burst stimulation with induced AF was 26.7% (8/30) in the LRDN group, which was significantly decreased compared with that of the Sham group (53.3%, 16/30) (P=0.035). In addition, AF duration was also significantly decreased in the LRDN group (13.3 ± 5.1 s) compared with that of the Sham group (20.3 ± 7.3 s, P=0.024). Conclusions. RDN via RAAC could cause cardiac neural remodeling and effectively inhibit AF inducibility and shorten AF duration. It may be useful in selecting therapeutic approaches for AF patients.